An evaluation on the floral phenology, developmental variation in fruit and seed, maturation period in (Pongamia pinnata) - Sarojini, Mahatma; Narayan, Ratan; Naidu, Viswanathan (Global Journal of Food and Agribusiness Management, 2017)
Pongamia pinnata is a leguminous tree having enormous potential of producing high seed oil that could be as a source of biofuel. The collection of pods with higher seed quality characters is much important for production of elite seedlings at nursery and hence studies related to seed maturation were initiated as matured seed is the basic character of quality seed. To evaluate the steps in obtaining quality seed from the tree, studies were initiated on floral phenology, fruit and seed maturation and on evaluation of fresh fruit colour variation on seed and seedling quality characters. The results revealed that in pungam, the flowers per inflorescence ranged from 28.4 to 44.0, and only 3-4 per cent of the flowers set as pods. But the seed set was obtained with 80 per cent of the pods. The studies on pod maturation revealed that seeds of pods attained physiological maturation at 26 weeks after anthesis and it was accompanied with the change in colour of pods from green to dark brown and the seed from greenish white to dark brown, where the seeds had potential for higher germination (98 per cent). Evaluation on harvest index based on fresh fruits colour (yellow, light brown and dark brown) revealed that the seeds of light brown fruits recorded the higher germination (96 per cent), and seedling quality characters suggesting the collection of light brown fruits for obtaining good quality seed for sowing. The colour of pods also coincided with the colour obtained with maturation of pod studied with tagged flowers